Community-based enterprises: The significance of partnerships and institutional linkages - Cristiana Simão Seixas; Fikret Berkes (International Journal of the Commons, 2009)
Community-based institutions used to be driven by local needs, but in recent decades, some of them have been responding to national and global economic opportunities. These cases are of interest because they make it possible to investigate how local institutions can evolve in response to new challenges. A promising set of cases comes from the UNDP Equator Initiative, a program that holds biennial searches to find and reward entrepreneurship cases that seek to reduce poverty and conserve biodiversity at the same time. What can we learn from these local entrepreneurship cases that seem to be playing at the global level? Here we focus on partnerships and horizontal and vertical linkages in a sample of ten Equator Initiative projects. We find that successful projects tend to interact with a large array of support groups, typically 10 to 15 partners. Based on information from on-site research, these partners include local and national NGOs; local, regional and (less commonly) national governments; international donor agencies and other organizations; and universities and research centers. These partners provide a range of services and support functions, including raising start-up funds; institution building; business networking and marketing; innovation and knowledge transfer; and technical training. These findings indicate that a diverse variety of partners are needed to help satisfy a diversity of needs, and highlight the importance of networks and support groups in the evolution of commons institutions.